The Ηellenic expeditionary force in korea : 1950-1955 (An Army History Directorate Publication, 2020)
Greece is one of the 22 States that participated in the Korean War of 1950-1955. After the Second World War Korea was divided along the length of the 38th parallel, of -latitude in North Korea, with an Eastern Orientation and South Korea, with a Western one. The attempts of the United Nations Organization for unification by means of elections failed. A situation of Cold War was, therefore, created up to 1950. At the same time, there were attempts made by North Korea to impose a Soviet-type status on South Korea-as well. The peak of these activities was the surprise unprovoked attack at 04:OO o’clock on the 25th of June, 1950, made by 10 North Korean divisions with approximately 240 T-34 tanks and 1400 artillery guns against South Korea. Within 4 days Seoul was seized.